Hubungan Pendidikan dan Pendapatan Orang Tua dengan Pertumbuhan Balita - Yulia Nur Khayati; Sundari Sundari (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2021)
The factors influencing the growth and development of children are internal factor, external factor which is prenatal factor, during giving birth factor and after giving birth factor. Prenatal factors include nutrition, mechanism, toxin, endoctrine, radiation, and mother’s psychological condition, while for the factors after giving birth are nutrition, psychological condition, social environment and stimulation. Family and culture factors involve parents’ job and income, educational levels and knowledge. The purpose of this research is to know the correlation between parents’ educational levels and income with the growth of children under five measured by using Body Weight/Body Height (BB/TB) and Body Height/Age (TB/A). The method applied analytical observational using cross sectional approach. The samples were children under five aged 0-5 years as many as 75 respondents. The technique to collect the data used WHO’s growth table consisting of body height per age (TB/U) and body weight per body height (BB/TB), parents’ job and income were collected by using questionnaires and analyzed bivariately by using chi Square test. The results of this research showed a correlation between parents’ educational levels and income with the growth (TB/U), a correlation between parents’ educational levels and the growth of the children (BB/TB) and no correlation between parents’ income with the growth of the children (BB/TB)